A colorimetric immunoassay for the detection of human vascular endothelial growth factor 165 (VEGF165) based on anti-VEGF-iron oxide nanoparticle conjugation - Ceylan, Hülya Kuduğ; Kırbay, Fatma Öztürk; Yazgan, İdris; Elibol, Murat (Springer Science and Business Media LLC, 2024)
AbstractVascular endothelial growth factor (VEGF) is an indispensable element in many physiological processes, while alterations in its level in the circulating system are signs of pathology-associated diseases. Therefore, its precise and selective detection is critical for clinical applications to monitor the progression of the pathology. In this study, an optical immunoassay biosensor was developed as a model study for detecting recombinant VEGF165. The VEGF165 sample was purified from recombinant Kluyveromyces lactis GG799 yeast cells. Indirect ELISA was used during the detection, wherein iron oxide nanoparticles (FeNPs) were utilized to obtain optical signals. The FeNPs were synthesized in the presence of lactose p-amino benzoic acid (LpAB). VEGF165 antibody was conjugated to the LpAB-FeNPs through EDC/NHS chemistry to convert the iron oxide nanoparticles into VEGF165 specific probes. The specificity of the prepared system was tested in the presence of potential serum-based interferents (i.e., glucose, urea, insulin, C-reactive protein, and serum amyloid A), and validation studies were performed in a simulated serum sample. The proposed immunoassay showed a wide detection range (0.5 to 100 ng/mL) with a detection limit of 0.29 ng/mL. These results show that the developed assay could offer a sensitive, simple, specific, reliable, and high-throughput detection platform that can be used in the clinical diagnostics of VEGF. Graphical Abstract
Keywords: Vascular Endothelial Growth Factor A; Immunoassay; Original Paper; Indirect Elisa; Vascular Endothelial Growth Factors; Iron Oxide Nanoparticle; Human Vascular Endothelial Growth Factor; Benzoic Acid; Humans; Colorimetry; Magnetic Iron Oxide Nanoparticles; Optical Detection